The Influence of Organizational Climate, Work Involvement, and Knowledge Sharing on Employee Performance - Kusuma, Dimas Hadi; Sukardi, Sukardi (Untag Business and Accounting Review, 2023)
This study aims to determine the effect of organizational climate, work involvement, and knowledge sharing on employee performance in the Semarang Tengah District Office, Semarang City. The population used was all employees of Semarang Tengah District with a total of 95 people, with the sampling technique using the census method or saturated sample, the size of the sample used was 95 respondents. The data source used is primary data, with the data collection method using a questionnaire. The data analysis technique used is multiple linear regression analysis. The results of hypothesis testing show that organizational climate has a positive and significant effect on employee performance, work involvement has a positive and significant effect on employee performance, and knowledge sharing has a positive and significant effect on employee performance. The coefficient of determination is 0.631, meaning that organizational climate, work involvement, and knowledge sharing can explain variations in employee performance variables by 63.1 percent, so it still needs to be followed up with further research, especially related to individual aspects and organizational commitment.